The Effect of Hypercholesterolemia on Cortical Bone Thickness of Wistar Rats (Rattus norvegicus) - Sofka, Auliya Dzaqiyatus; Lestari, Pudji; Sari, Gadis Meinar (Folia Medica Indonesiana, 2019)
There have been several studies reporting the effect of hypercholesterolemia on cortical thickness, but it remains a controversy. Some studies suggest that hypercholesterolemia can decrease osteoblast activity and increase osteoclast activity. Meanwhile other studies suggest that hypercholesterolemia is a protective factor of osteoporosis. Therefore, it is necessary to conduct a study to determine the effect of hypercholesterolemia on cortical bone thickness. Method: This study used 8 rats (Rattus norvegicus) that were divided into 2 groups, including control group (K0) that was given standard diet and experimental group (K1) that was given high fat diet for 28 days and all were executed to obtain the femur bone. The cortical bone thickness was measured by using Optilab Viewer and Optilab Image Raster software. Result: The data analysis was conducted using independent t-test. A p value of <0.05 is considered significant. The results showed that hypercholesterolemia had significant effect on cortical bone thickness. The average cortical bone thickness in the control group was 146.92 µm whereas in the experimental group was 124.53 µm, the mean difference between the two groups was 22.39 µm. There was a 6% decrease of cortical bone thickness. In conclusion, hypercholesterolemia can decrease cortical bone thickness of wistar rats (Rattus norvegicus).